PESANTREN MANHAJ SALAFI: PENDIDIKAN ISLAM MODEL BARU DI INDONESIA - Irham, Irham (ULUL ALBAB Jurnal Studi Islam, 2016)
This article explains the devolopment of Islamic education in Indonesia, especially in pesantren (Islamic Boarding School) which is salafi manhaj. It aims at finding islamic education model developed at salafi manhaj pesantren. It uses library research. This article concludes that salafi manhaj pesantren currently becomes new model of Islamic education in Indonesia. This model differs from those applied in most pesantrens in Indonesia. The factor triggering its development is the effect of the transnational of Islam. This factor can further complete the theory of Islamic education change in Indonesia proposed by Karel Steenbrink.